PERLINDUNGAN HUKUM HAK ULAYAT MASYARAKAT ADAT SUKU TAMBEE DI KABUPATEN LUWU TIMUR - Ismail Th. Sapiu (Jurnal HUKUM BISNIS, 2023)
Ulayat rights are a series of authorities and obligations attached to a customary law community. Indigenous peoples are a group of people who have the same cultural identity, live for generations in the same geographical area based on ties of ancestral origins, have wealth and customary property that are jointly owned and have customary institutions or norms. This research uses normative juridical research methods, namely analyzing a legal problem with applicable rules. Whereas the existence of the Tambee tribe community existed before the independence of the State of Indonesia until now, the village inhabited by the Tambee tribe has abundant natural potential supported by a fairly large area. Bearing in mind that land has economic value, ulayat land located in the village must be safeguarded for assets. That form of legal protection for ulayat land located in a ulayat village must be certified in order to protect and provide legal certainty in the form of a certificate. Whereas the safeguarding of communal land assets is carried out first by stipulating communal land by the local Regional Government by requiring the support of local law enforcement officers. After obtaining a decree, the land is registered at the local land office for measurement and a land parcel identification number is issued as the basis for land registration. Keywords : Customary law community, Tambee Tribe, Government of East Luwu